Medios y recursos didácticos audiovisuales y su influencia en el rendimiento escolar en el área de ciencia tecnología y ambiente de los estudiantes de 1er grado de secundaria de la I.E N°00170 de la Naciente de Río Negro - Gonzáles Pérez, Alex (2011)
The research aimed to determine the influence of media and educational resources audiovisual school performance in the area of science technology and environment of students in first grade of Secondary Education of School No. 00170 of the Rising Black Riverin 2010. The empirical data was collected from 27 students in first grade high school of School No. 00170, which developed a test before and after attending training sessions with the use of audiovisual media and educational resources. The collected data were processed using frequency distribution to identify levels of student performance, and for testing hypotheses by distributing T- Student with a 5% significance level and degrees of freedom (N-1 ). The results showed that the media and audiovisual teaching resources developed significantly both dimensions in the area of Science, Technology and Environment, at the level of understanding of information reach the very high category (Te: 15.71 greater than Tt: 1. 71) and in finding and testing the very high category (Te: 12.45 greater than Tt: 1.71). The application of audiovisual media and educational resources significantly influence school performance of students in the first grade of secondary education of School No. 00170 of the Rising Black River, reaching the high category (Te: 14.99 higher than Tt: 1.71).